ANALISIS TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN METODE COBIT 4.1 (Studi Kasus PUSDIKLAT APARATUR KEMENKES RI) - Titin Kristiana (Jurnal Techno Nusa Mandiri, 2016)
Information technology governance in the process of data management is an important asset to the agency. Governance of information technology in data management processes that are less goodwill pose some problems. The problem that occurs is data loss, data leaks, misuse of computers and even common decision-making errors also due to incorrect calculations. This indicates the ineffectiveness of information technology governance in the Indonesian Ministry of Health PUSDIKLAT apparatus. PUSDIKLAT apparatus Ministry of Health of Indonesia as government agencies that conduct education and training of health personnel requires an information technology governance both in the process of data management in its operations. The purpose of this paper is to obtain information about the state of information technology governance and analyze gaps. The framework used is COBIT 4.1 by using the DS and ME domain. The results of these research findings are the maturity level of the current state of information technology governance in the Indonesian Ministry of Health officials PUSDIKLAT are at level 2 and the conditions are expected to reach level 3. Then do an analysis of the gap and then made a recommendation strategies to address the existing gaps in order to rate maturity are expected to be achieved. Therefore, it can be concluded that there is still a gap between the current maturity level at level 2 with the expected maturity level at level 3.